Strategi pengelolaan kantin sehat - Dian Maulidawati; Zahtamal Zahtamal; Rahman Karnila (Jurnal Zona, 2022)
This study aims to (1) analyze the factors of physical environmental conditions and sanitation in realizing a healthy canteen (2) analyze the behavior of food handlers in realizing a healthy canteen on the Riau University campus (3) analyze policies related to efforts to create a healthy canteen on the Riau University campus (4) analyze the formulation of strategies and recommendations to realize a healthy canteen on the Riau University campus. This research was conducted in 8 canteens at the Riau University Campus, Pekanbaru City, which are located at the Bina Widya Campus, Gobah Campus and Diponegoro FK Campus. The tools and materials in this study used in this study were the meter, luxmeter, questionnaire, interview sheet which was used to measure the variables studied, by filling out the question sheet. This study uses a quantitative descriptive design approach, to obtain factors of environmental conditions and sanitation as well as food handler behavior. Data collection techniques used in this study were questionnaires, interviews and observations. Data on factors of physical environmental conditions were taken by observation, including canteen sanitation facilities and canteen equipment sanitation. Data on the hygiene factors of food handlers were taken by means of questionnaires and observations. The data taken include personal hygiene of food handlers, nail hygiene, use of aprons and shoes when cooking and hand washing habits. All data will be compared with the Regulation of the Minister of Health of the Republic of Indonesia Number 1096/MENKES/PER/VI/2011 concerning Food and Service Sanitation Hygiene. The entire data that has been collected is tabulated in a table and analyzed descriptively using Microsoft Excel software.Based on the research data, it is known that from the sanitation indicators assessed, some canteens still cannot meet the requirements to realize a healthy canteen. the results of the assessment of the behavior of food handlers amounted to 8 people, there were 4 (50%) respondents who behaved less well, 4 (50%) respondents behaved quite well and no respondents behaved very well. Bad behaviors include not washing hands after defecating, not using PPE such as headgear and aprons, and smoking behavior. And there is still a lack of knowledge of handlers about healthy canteens, and knowledge related to sanitation and hygiene. The quadrant position for the healthy canteen management strategy at the UNRI campus based on the IFAS value of 1.33 and the EFAS value of 1.23 lies in quadrant I or the SO strategy. SO strategy is an aggressive strategy that uses internal strengths to take advantage of external opportunities. The strategy that can be applied is by conducting regular canteen supervision and improving healthy canteen policy soup and personal hygiene supervision for food handlers. Based on the research that has been done regarding the management of healthy canteens on the UNRI Campus, several things can be suggested, namely. (1) for further researchers, it is necessary to carry out further studies related to food equipment, food ingredients, and healthy food presentation in realizing a healthy canteen on the UNRI campus, (2) it is necessary to strengthen the healthy canteen policy on the UNRI campus. (3) the canteen owner is expected to improve the hygiene and sanitation of the canteen more optimally by increasing healthy behavior, especially for food handlers.